The 13th Kilbrandon Lecture – University of Strathclyde, 19 November 2015 – Leadership and child protection - Alexis Jay (Scottish Journal of Residential Child Care)
Ladies and gentlemen, I am delighted and not a little alarmed to have the privilege of delivering the Kilbrandon Lecture this evening. My theme tonight is leadership particularly focused on child protection. Over the years, like many of you here, I have had to complete questionnaires about personality traits and decision making preferences which are then converted into leadership styles. There was The KAI score on the adaptive innovative continuum, the Myers Briggs scales, and various colour related tests, to mention the ones I can remember, all derived from psychometric testing and interpretation whose validity has subsequently been called into question. The body of knowledge and theory about leadership is mostly dull and dry as dust - and so unlike the many colourful leaders we are familiar with.